Comparison of mechanical properties of polyester composites reinforced with autochthonous natural fibres: flax and hemp - Rocha, João (2017)
Nowadays, increasing pollution is causing climate change, and therefore the need to reduce carbon footprints has brought the growing use of autochthonous natural materials. On the other hand, there is new demand from the world population that requires the increased use of recyclable materials, and natural fibres are excellent candidates for this role. However, only in the last few years has this subject been studied for technical applications [1]. Natural fibre is a very interesting material, and in association with a matrix it forms a composite material. Natural fibre composites (NFCs) have some advantages compared with synthetic ones, with the most relevant being their lower density and higher specific strength and stiffness. Furthermore, they are a renewable resource whose production requires little energy and involves CO2 absorption. Nevertheless, NFCs also have disadvantages, such as lower durability when compared to synthetic fibre composites, although this can be improved significantly with specific treatments; a greater variability of properties; and the fact that they suffer from higher moisture absorption, which results in swelling [2].